A Single Motor Donor Nerve for Two Functional Free Flaps in Facial Reanimation - Omar Hausien, MBBChir, MA (Cantab), MRCS; Lucia Pannuto, FEBOPRAS; Kallirroi Tzafetta, FRCS(Plast) (Plastic and Reconstructive Surgery, Global Open)
Summary:. Bilateral facial palsy with multiple cranial nerve involvement presents a reconstructive challenge. We report the use of a single donor nerve, the masseteric nerve, for the reinnervation of 2 free functioning gracilis flaps in a pediatric case of bilateral facial palsy. A 9-year-old child was referred to our center following excision of a cerebellar tumor (pilocytic astrocytoma). This resulted in multiple cranial nerve palsies including bilateral facial, abducens, and left masseteric nerves. Relevant clinical findings were a mask-like face, drooling, incomplete eye closure, and swallowing and speech difficulties. A 3-stage approach was utilized to achieve bilateral smile reanimation using a single donor nerve and avoid any further functional deficits. In the first surgery, the available right masseteric nerve main branch was coapted to a cross-facial nerve graft (sural nerve graft). In the second surgery, this graft was then split proximally, with half used to power an ipsilateral free functioning gracilis flap, and the remaining half later used to power a contralateral gracilis flap at the third stage. Good commissure excursion, more than 10 mm, was achieved bilaterally, with both flaps contributing to a symmetrical and synchronous smile. Spontaneity was developed, attributed to neuronal plasticity and physiotherapy input. In our experience, this technique is a valid option for smile restoration in pediatric patients with bilateral facial palsy who have only 1 of 2 masseteric nerves available for transfer.